General pathogenetic links: Chronic heart failure and osteoporosis. (Eurasian Medical Research Periodical, 2024)
Human Fc gamma-receptor II alpha (FcγRIIA) Polymorphism has been linked with predisposition to susceptibility and/or severity degrees of several infectious diseases. To find if there is any link between these genetic polymorphisms and the intensity of the severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) disease. FcγRIIA polymorphism has been evaluated in the DNA extracts of 100 SARS-Cov-2 patients from Iraq. The participants included 74 mildly and moderately infected patients and 26 severely infected patients. A significant correlation was detected among FcγRIIA-131 polymorphism and severity of COVID-19, with higher frequency of FcγRIIA G/G 131 homozygote in severely infected individuals compared to that in the mildly/moderately infected patients in codominant and recessive mode; (p = 0.004 and p = 0.003), respectively. While AG and AA genotype could act as a protective factor. The outcomes demonstrate that FcγRIIA polymorphic genotype may affect the severity of the SARS-Cov2